Early Outcomes of a Next-Generation Balloon-Expandable Transcatheter Heart Valve - The Myval System: A Single-Center Experience From Serbia - Boljevic, Darko; Bojic, Milovan; Farkic, Mihajlo; Sagic, Dragan; Hinic, Sasa; Topic, Dragan; Dobric, Milan; Lakcevic, Jovana; Nikolic, Marko; Veljkovic, Stefan; et al. (Journal of Cardiology and Cardiovascular Medicine, 2023)
Transcatheter aortic valve implantation (TAVI) is one of the most effective treatments for severe aortic valve stenosis (AVS). Different genres and generations of transcatheter heart valves (THVs) are accessible, offering operators an opportunity to choose a patient-tailored device. In this single-center study, we present the outcomes of Serbian patients treated with next-generation Myval THV for severe symptomatic AVS. Myval THV was implanted in all consecutive patients who underwent TAVI at the Dedinje Cardiovascular Institute of Belgrade, Serbia between October 2020 and September 2021. The primary endpoint was device success on day 30. Secondary endpoints included 30-day all-cause mortality, cardiovascular death, stroke, moderate/severe paravalvular leak (PVL), and new permanent pacemaker implantation (PPI). TAVI was performed as per the European Society of Cardiology guidelines. The study comprised thirteen patients, aged 72 ± 13 years with mean EuroSCORE (7.17%) and Society of Thoracic Surgeons (2.72%,) scores who underwent TAVI successfully with 92.3% using the percutaneous approach. Myval THV intermediate and extra-large sizes were implanted in 46% and 15% of patients, respectively. This acute procedure success rate was 100%. The primary composite endpoint of early device success was achieved in all patients. None of the patients had clinically significant aortic regurgitation or moderate/severe PVL. No patient experienced stroke, contrast-induced acute kidney injury, device-related vascular complications, or a new PPI. The all-cause mortality rate at 30 days was 0%. Myval THV system demonstrated a favorable safety/efficacy profile within 30 days post-procedure at a single center in Serbia. This is the first report of my experience with Myval THV from Serbia.